The internal forum in the framework of the Church law - FABRIS, CONSTANTINO-M. (Prawo Kanoniczne, 2017)
The paper presents the concept of the internal forum in the framework of the Church law. First of all traces the birth of the concept of internal forum and the latest evolution in the legal canon law; particular attention is devoted to the developments of the Code of this institution. It goes on to analyze the skills and functioning of the court seised in the inner hole: the Tribunal of the Apostolic Penitentiary.